Enrichment on High Utility Sub Graph Mining on Transactional Database - M, Akshatha H; M, Geethika M; K, Suresh (International Journal of Psychosocial Rehabilitation, 2020)
Enrichment on High utility item set that produces a great deal of benefit for the seller. High utility item set mining is an effective technique for dynamic huge data. Fundamentally the database that contains products with amounts and mining ability is limited to transaction data consist of items. Graph mining is a non- trival graph structure from a confounded system. In the proposed technique that we are going to change over the transaction database into sub graph structure. By utilizing high utility sub graph mining calculation and it produces yield as a graph structure.